The Rise and Decline of the Zairian State - Young, Crawford, 1931- (Book collections on Project MUSE., 1985)
Zaire, apparently strong and stable under President Mobutu in the early 1970s, was bankrupt and discredited by the end of that decade, beset by hyperinflation and mass corruption, the populace forced into abject poverty. Why and how, in a new state strategically located in Central Africa and rich in mineral resources, did this happen? How did the Zairian state become a "parasitic predator" upon its own people? The authors examine the political history of Mobutu's Zaire, looking at critical structures and patterns of societal flux, inequality, and cleavage, in particular the urban-rural nexus, the problematic of class formation, and the fluid patterns of cultural pluralism.